スキャノラ®における下顎のパノラマ像の歪み - 上野, 徹; 岡村, 清; 福西, 啓八; 中根, 高信; 岡, 達郎; 藤井, 和則; 山根, 進; 船橋, 賢市; 篠崎, 文彦 (Journal of Japanese Society of Oral Implantology, 1999)
In oral implant treatment, panoramic radiography is neccessary. It is important that horizontal light beam agrees with occlusal plane for good panoramic radiography. Thns, in order to investigated changes of shape and location in the mandibular area using SCANORA®, an ideal arch was nade of polimethylmethacrylate, the steel balls were set at the points of Cuspid, second Premolar and second Molar of right side and panoramic radiography was peifored with differences of zero, 10, 20 and 30 degree between horizontal light beam and occulusal plane. As for changes of shape, from zero to 20 degree, change rates of shape were nearly equal, but at 30 degrees, they were different from the others. As for changes of location, horizontal change rates of location between steel balls increased in the mesial area with the increase of incline of the occlusal plane. Vertical change rates of distance between stell balls reduced with the increase of the incline of the occlusal plane. The resalts were charcteristic of the rebolution orbit of panoramic radiography.